Oracle Database 10g performance tuning tips & techniques - Niemiec, Richard J. (McGraw Hill professional., 2007)
Database professionals typically spend 40 percent of their time on tuning. Approximately half of the material in this edition will be all-new. Previous edition has sold 10,000 copies.